Development of emulgel technology with saw palmetto extracts and of japanese sophora tincture for androgenetic alopecia treatment - I. O. Yarema; M. I. Feodorovska; N. P. Polovkо (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Androgenic alopecia is a hair disease caused by an excessive influence of androgens on hair follicles, whose treatment requires long-term use of systemic and / or local action drugs. In Ukrainian pharmaceutical market for the androgenic alopecia treatment synthetic drug minoxidil is presented, which in the local long-term application causes many side effects. Therefore, the drugs development of plant origin is important. Taking into account of the androgenic alopecia pathogenesis, it was developed the emulgel composition and technology, which has Saw Palmetto extract and Sophora Japonica tincture as active ingredients. Their main biological active substances applying topically provide anti-androgenic, venotonic and follicles protective action. The qualities of dermatological remedies in large measure are influenced by their technological process. Therefore, the purpose of this investigation was the development of a rational emulgel technology with Saw Palmetto extract and Sophora Japonica tincture for the androgenic alopecia prevention and treatment. Samples of emulgel were manufactured with applying of different technological methods, namely: the method of emulsification, temperature, rate and duration of stirring. Prepared samples were controlled by uniformity, dispersion degree (with microscope Delta Optical Genetic Pro, Poland), pH (with pH-meter 150 MI, Russia) and structure viscosity (with rotational viscometer Brookfield VR-3000, Myr VISKOTECH, Spain). The optimal temperature for the emulgel preparation is 60 °C, since the melting temperature of cetyl alcohol (the most refractory component of the formulation) is 52 °C. When choosing the emulsifying method it was found that sequential addition of hydrophilic and oil phases to emulgators provided the highest dispersion and optimally rheological properties of the emulgel. The best homogenization speed, providing a high degree of dispersion and structural viscosity in the range 3 200-3 400 mPas, is 2 000 rev/min. The intensive size reduction of the dispersed phase was observed for 30 min stirring. As a result of investigation, it was established that the best method of emulsification was the sequential adding of oil and aqueous phase to the mixture of emulsifiers at the temperature - 60 °C, the speed - 2 000 rev/min for 30 min.